Multiple, zonal and multi-zone adenoma detection rates according to quality of cleansing during colonoscopy. Issue 6 (December 2016) - Pontone, Stefano; Hassan, Cesare; Maselli, Roberta; Pontone, Paolo; Angelini, Rita; Brighi, Manuela; Patrizi, Gregorio; Pironi, Daniele; Magliocca, Fabio Massimo; Filippini, Angelo
Background: The safety and diagnostic accuracy of colonoscopy depend on the quality of colon cleansing. The adenoma detection rate is usually used as a quality measurement score. Objective: We aimed to introduce and evaluate three new parameters to determine polyps and adenomas segmental localization and their distribution in association with different bowel preparation levels during colonoscopy. We introduce the multiple adenoma detection rate (the percentage of patients with >2 adenomas diagnosed during colonoscopy), the zonal adenoma detection rate (the percentage of patients with >2 adenomas diagnosed during colonoscopy in different colon areas (rectum, sigmoid, descending, transverse, ascending and cecum colon)), and multi-zone adenoma detection rate (the percentage of patients with >2 adenomas diagnosed during colonoscopy in different colon areas with at least a segment between them with or without lesions (i.e. rectum and descending colon with or without lesions in the sigmoid)). Methods: We prospectively enrolled outpatients who underwent colonoscopy from January 2013 to October 2014. The bowel preparation quality, according to the Aronchick modified scale, number and location of lesions, Paris classification and histology, were recorded. The multiple adenoma/polyp detection rate, zonal adenoma/polyp detection rate, and multi-zone adenoma/polyp detection rate were determined. Results: In total, 519 consecutive patients (266/253 M/F; mean age 55.3 ± 12.8 years) were enrolled. The adenoma and polyp detection rates were 21% and 35%, respectively. Multiple adenomas were detected in 28 patients. Adenoma and polyp detection rate and new parameters were statistically significantly higher in the optimal as compared with the adequate bowel preparation. Conclusions: An optimal level of bowel preparation was strongly associated not only with a higher adenoma detection rate, but also with a higher chance of detecting multiple clinically relevant lesions in adjacent or discrete segments of the colon.